Ketentuan dan Akibat Hukum terhadap Penghapusan dan Pemusnahan Barang Milik Negara (ASET) Berdasarkan Peraturan Menteri Keuangan - Masriyani Masriyani; Vira Sekar Ningrum (Wajah Hukum, 2020)
The central issue in the management system of State-Owned Goods (assets) is the implementation of the management of State-Owned Goods (assets) based on functional principles, legal certainty, transparency, efficiency, accountability, and certainty of value. Decree of the Minister of Finance No. 470/KMK.01/1994 on Procedures for the Elimination and Utilization of Property. State Wealth, Decree of the Minister of Finance No. 350/KMK.03/1994 on The Procedure for Exchanging Property/State Wealth. In terms of regulations, the provisions are still many weaknesses, especially in the field of the legal system is still partial, where the regulations are not yet integrated and thorough, each of these regulations still overlaps and stands alone so that it is not a union and has nothing to do between the regulations below and the above in a matter of the policy of the management of State Owned Goods (BMN). This writing aims to understand and understand how the legal consequences generated from the legal system governing the removal of state property by using the approach method is a statutory approach. So that the results of the writing can provide an overview and analysis of the issue of the removal and destruction of state-owned goods as not yet regulated in the special legislation.